International standards and codes and financial stability - Vasudevan, A. (2001)
Efforts at implementing standards and codes without concomitant adoption of sound macroeconomic and structural policies are unlikely to ensure growth with financial stability. Emerging market economies undertaking financial reforms have to adopt not one or two but a requisite set of standards and codes in order to promote the twin objectives of growth and financial stability. The process of transmission discussed here shows that information and expectations play a major role in market calculus in undertaking investment decisions and resource allocative functions. - Reproduced
Keywords: Standards; Finance